Pathogenesis-related protein 10 in resistance to biotic stress: progress in elucidating functions, regulation and modes of action - Lopes, Natasha dos Santos; Santos, Ariana Silva; de Novais, Diogo Pereira Silva; Pirovani, Carlos Priminho; Micheli, Fabienne (Frontiers in Plant Science, 2023)
Family 10 pathogenesis-related proteins (PR-10) are widely distributed in the plant kingdom. They are multifunctional proteins, constitutively expressed in all plant tissues, playing a role in growth and development or being induced in stress situations. Several studies have investigated the preponderant role of PR-10 in plant defense against biotic stresses; however, little is known about the mechanisms of action these proteins perform. This is the first systematic review conducted to gather information on the subject and reveal the possible mechanisms of action that PR-10 performs. Therefore, we searched three databases (PubMed, Web of Science and Scopus). To avoid bias, a protocol with inclusion and exclusion criteria was previously prepared. In total, 216 articles related to the proposed objective for this study were selected. The participation of PR-10 was revealed in the plant’s defense against several stressor agents such as viruses, bacteria, fungi, oomycetes, nematodes and insects, and studies involving fungi and bacteria were predominant in the sample. Studies with combined techniques showed a compilation of relevant information about PR-10 in biotic stress that collaborate with the understanding of the mechanisms of action this molecule performs. The upregulation of PR-10 was predominant under different conditions of biotic stress over time, in addition to being more expressive in resistant varieties both at the transcriptional and at the protein level. Biological models have been proposed that reveal an intrinsic web of molecular interactions involving PR-10 modes of action. These include hormonal pathways, transcription factors, physical interactions with effector proteins or pattern recognition receptors (PRRs) and other molecules involved with the plant's defense system. The molecular web involving PR-10 reveals how the plant's defense response is mediated, either to trigger susceptibility or, based on data systematized in this review, more frequently, to have plant resistance to the disease.